Molecular Doping Enhances Photoconductivity in Polymer Bulk Heterojunction Solar Cells. (19th September 2013) - Zhang, Yuan; Zhou, Huiqiong; Seifter, Jason; Ying, Lei; Mikhailovsky, Alexander; Heeger, Alan J.; Bazan, Guillermo C.; Nguyen, Thuc‐Quyen
<x xml:space="preserve">Abstract</x> Addition of low concentrations (<1:100, dopant:donor) of a fluorinated p‐type dopant, F4‐TCNQ leads to a considerable enhancement of the photocurrent in PCDTBT:PC70BM bulk heterojunction solar cells. As a result, the power conversion efficiency increases from 6.41% to 7.94 %. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>